. Penataan Ulang Kewenangan Bakamla dalam Sistem Penegakan Hukum Laut di Indonesia - Habib Ferian Fajar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Maritime security and safety are critical issues for Indonesia as an archipelagic nation with vast maritime territories and an ever-evolving landscape of threats. Stemming from overlapping jurisdictional issues among agencies, particularly Bakamla, there appears to be a lack of harmony in the applicable legal framework, which is further exacerbated by the ambiguity of Bakamla’s jurisdictional boundaries. This has led to arbitrary coercive actions, such as the detention and seizure of vessels, carried out without clear procedures. This study employs a normative approach through a literature review, demonstrating that such regulatory fragmentation triggers jurisdictional conflicts and contributes to weak maritime law enforcement. Consequently, a restructuring is necessary through the strengthening of Bakamla’s authority, regulatory harmonization, integration of command systems, institutional oversight and alignment with the 1982 UNCLOS based on the values of Pancasila.